P1-S4.22 Impact of a hypothetical chlamydia vaccine on population prevalence: a mathematical Modelling Study. (10th July 2011) - Heijne, J; Althaus, C; Herzog, S; Low, N
Abstract : Background: It has not yet been possible to develop a Chlamydia trachomatis (chlamydia) vaccine but research to achieve this continues. It is therefore important to evaluate the potential impact of different chlamydia vaccine strategies on population prevalence. The optimal strategy might differ depending on whether a vaccine prevents chlamydia infection, or prevents ascending infection to reduce the risk of long term complications. Here, we used a mathematical model to focus on vaccination strategies that aim to reduce population prevalence. Methods: We developed a deterministic pair model of heterosexuals aged 15–39 years that incorporates the formation and dissolution of sexual partnerships. We used sexual behavioural data from UK population-based studies to inform the model. The model has a baseline chlamydia prevalence of 3%. In all strategies examined, vaccination was introduced before sexual debut. We investigated the impact on population prevalence of different types of vaccine coverage, vaccine efficacy and duration of protection. We also assumed different types of protection after vaccination. We started with full protection, but since animal models have shown that sterilising immunity is difficult to achieve we also investigated partial protection of the vaccine by assuming a decreased susceptibility to infection after vaccination or, when infected, a shorter duration of infection or a reduced transmission probability. Results: The impact of different vaccination strategies on chlamydia population prevalence depends on the characteristics of the vaccine. In the best case scenario, where the vaccine coverage and efficacy is 100% and duration of protection lifelong, it takes about 7 years to half the prevalence. With an average duration of protection of 10 years, a vaccine coverage or vaccine efficacy of around 70% or higher per year was needed to half the chlamydia prevalence in 10 years. For high vaccine coverage levels, the impact of vaccinating women alone on population prevalence was greater than vaccinating both men and women. The potential impact of a vaccine on chlamydia population prevalence was sensitive to the duration of protection of the vaccine and the vaccine efficacy. Conclusion: The model suggests that the impact of vaccination strategies on chlamydia prevalence highly depends on characteristics of future vaccines. Current efforts in vaccine development should be accompanied by mathematical models to investigate the optimal strategies.